2023
DOI: 10.1007/s00442-023-05323-y
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with disjunct populations of vascular plants: implications for assessing the effect of climate change

Abstract: Species distribution models are the most widely used tool to predict species distributions for species conservation and assessment of climate change impact. However, they usually do not consider intraspecific ecological variation exhibited by many species. Overlooking the potential differentiation among groups of populations may lead to misplacing any conservation actions. This issue may be particularly relevant in species in which few populations with potential local adaptation occur, as in species with disju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Chardon et al (2023) found that microhabitat variables weakly predict recruitment and seedling survival, with varied responses to environmental factors across species and life stages (Chardon et al, 2023). Adding to this complexity, a recent research has highlighted the importance of considering intraspeci c ecological variation when predicting species distributions for conservation and climate change impact assessment (Varaldo et al, 2023).…”
Section: Older Versions Ofmentioning
confidence: 99%
“…Chardon et al (2023) found that microhabitat variables weakly predict recruitment and seedling survival, with varied responses to environmental factors across species and life stages (Chardon et al, 2023). Adding to this complexity, a recent research has highlighted the importance of considering intraspeci c ecological variation when predicting species distributions for conservation and climate change impact assessment (Varaldo et al, 2023).…”
Section: Older Versions Ofmentioning
confidence: 99%